2016
DOI: 10.1103/physrevx.6.041040
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and String Breaking forQED2in the Hamiltonian Picture

Abstract: The formalism of matrix product states is used to perform a numerical study of (1+1)-dimensional QED -also known as the (massive) Schwinger model -in the presence of an external static 'quark' and 'antiquark'. We obtain a detailed picture of the transition from the confining state at short interquark distances to the broken-string 'hadronized' state at large distances and this for a wide range of couplings, recovering the predicted behavior in both the weak-and strong-coupling limit of the continuum theory. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 114 publications
9
112
0
Order By: Relevance
“…In [64] we found that the string tension σ α , see fig. 15a, interpolates smoothly between the behavior in the strong-coupling limit for small values of m/g and the weak-coupling limit for large values of m/g.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…In [64] we found that the string tension σ α , see fig. 15a, interpolates smoothly between the behavior in the strong-coupling limit for small values of m/g and the weak-coupling limit for large values of m/g.…”
Section: Resultsmentioning
confidence: 84%
“…(9) and (11), depends on a finite number of parameters. Similar as in [64] we block site 2n − 1 and 2n into one effective site n. Hence, the MPS ansatz for the ground state reads:…”
Section: Gauge Invariant Mpsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, methods based on tensor networks, such as matrix product states (MPS), have revealed themselves as valid candidates to explore the Hamiltonian formulation of LGT. Tensor networks, originally developed in the realm of quantum information theory, do not suffer from the sign problem and during the last years they have already been successfully applied to LGT problems and have demonstrated their power for mass spectra [5,6,7], thermal states [8,9,10] and phase diagrams [11] as well as for simulating dynamical problems for both Abelian and non-Abelian gauge theories [6,12]. Recently, we used MPS to compute the phase structure of the two-flavor Schwinger model with finite chemical potential [13] and performed a lattice calculation, with full extrapolation procedure until the proper continuum limit, in a regime where the sign problem occurs.…”
Section: Introductionmentioning
confidence: 99%